The Dimensional Change of Resin Denture Base After Immersion of Cinnamomum burmannii Extract and Chlorhexidine Solution - Wahyuni, Siti; Nawia, Femy (Dentika: Dental Journal, 2023)
Heat-cured acrylic resin is the most commonly used denture base material due to its biological, mechanical, chemical, and physical properties. Denture cleaning, which is essential for successful denture use, can be facilitated by utilizing cinnamon extract Cinnamomum burmannii 20% and chlorhexidine 0.2% as effective cleaning agents. However, these materials can affect the physical properties of denture, such as a dimensional change. The design of this study is experimental laboratories, aimed at identifying the effect of immersing denture base in extract Cinnamomum burmannii 20% and chlorhexidine 0.2% for 1 year (92 hours) to dimensional change of heat-cured acrylic resin. The sample consists of 30 heat-cured acrylic resin with sizes 65 mm x 10 mm x 2.5 mm, divided into 3 groups of treatment. After the entire study design has been carried out, data was analyzed by Univariat and one-way Anova and the result showed the significant of p = 0,001 (p<0,05). In this study, it was seen the the value of the dimensional change that was immersed in extract Cinnamomum burmannii 20% resulted in a smaller dimensional change value compared to chlorhexidine 0.2%.